Case report: Tracing in parallel the salivary and gut microbiota profiles to assist Larotrectinib anticancer treatment for NTRK fusion–positive glioblastoma - Turco, Luigia; Della Monica, Rosa; Giordano, Pasqualina; Cuomo, Mariella; Biazzo, Manuele; Mateu, Baptiste; Di Liello, Raimondo; Daniele, Bruno; Normanno, Nicola; De Luca, Antonella; Rachiglio, Anna Maria; Chiaramonte, Carmela; et al. (Frontiers in Oncology, 2024)
Oncotherapy can shape intestinal microbiota, which, in turn, may influence therapy effectiveness. Furthermore, microbiome signatures during treatments can be leveraged for the development of personalised therapeutic protocols in cancer treatment based on the identification of microbiota profiles as prognostic tools. Here, for the first time, the trajectory of gut and salivary microbiota in a patient treated with Larotrectinib, a targeted therapy approved for diagnosed glioblastoma multiforme neurotrophic tyrosine receptor kinase (NTRK) gene fusion-positive, has been accurately investigated. We based our analyses on histological diagnosis, genomic and epigenomic profiling of tumour DNA, and faecal and salivary full-length 16S rRNA gene sequencing. The study clearly evidenced a remodelling of the bacterial communities following 1 month of the NTRK-inhibitor treatment, at both gut and oral levels. We reported a boosting of specific bacteria also described in response to other chemotherapeutic approaches, such as Enterococcus faecium, E. hirae, Akkermansia muciniphila, Barnesiella intestinihominis, and Bacteroides fragilis. Moreover, several bacterial species were similarly modulated upon Larotrectinib in faecal and saliva samples. Our results suggest a parallel dynamism of microbiota profiles in both body matrices possibly useful to identify microbial biomarkers as contributors to precision medicine in cancer therapies.